ANALYSIS OF FOOD SECURITY INDEX IN EAST JAVA: A SPATIAL APPROACH AND POLICY PROJECTION - Mochammad Iskandar Zulkarnain; Syarif Imam Hidayat; Noor Rizkiyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze food security in East Java Province using a quantitative spatial approach and statistical projection. Secondary data from 2019 to 2023 were obtained from BPS (Statistics Indonesia), BKP (Food Security Agency), and the Ministry of Agriculture, covering indicators of food availability, accessibility, and utilization. The analysis was conducted using ArcGIS software for map visualization and the Single Exponential Smoothing (SES) method for projecting the Food Security Index for 2024. Spatial analysis revealed disparities in food security across regions: northern and western districts tend to be classified as "very resilient," while eastern regions and Madura Island, such as Bangkalan and Bondowoso, remain in the "resilient" category with high vulnerability levels. The 2024 Food Security Index projection presents three scenarios: optimistic (91.62), moderate (82.94), and pessimistic (73.91). Food security is strongly influenced by poverty, low Farmer’s Terms of Trade (NTP), limited infrastructure, and dependence on rice commodities. This study emphasizes the importance of data-driven policies, strengthening food distribution systems, investing in women’s education, and utilizing geospatial technology for monitoring and mitigating food crises. These findings reinforce the view that high food production alone does not guarantee food security without equitable access and adequate nutritional utilization. The study provides a foundation for formulating sustainable food security strategies aligned with Sustainable Development Goal (SDG) number 2.